Fake news, desinformação e deslegitimação do processo eleitoral brasileiro: uma análise sob a perspectiva da jurisprudência do Tribunal Superior Eleitoral nas eleições 2022 - Queiroz, André Vieira (2023)
The disruption in the communicative model, caused by the technological revolution of recent decades, in addition to elevating internet users to a position of protagonists in the circulation of information, has fostered the amplification of visceral, extremist and denialist discourses, triggering a progressive lack of interest in the truth of facts. In the political field, this phenomenon, called post-truth, perfected a surreptitious kind of democratic erosion, which acts to delegitimize the electoral process based on the cognitive manipulation of voters through the propagation of misleading content. Starting from these premises, the present study aims to conceptualize the informational disorder from the analysis of the TSE jurisprudence, related to the 2022 elections. The problem that arises can be synthesized in the following question: what are the main parameters pointed TSE, in the 2022 Elections, as necessary for the characterization of informational disorder with electoral relevance? The hypothesis is that, given the legislator's inertia, the ascending institutional crisis and the serious democratic risks arising therefrom, the TSE would have adopted a more proactive stance in the 2022 Elections, assuming responsibility for setting the standards of electoral information disorder. The justification for carrying out this study is demonstrated, firstly, in its actuality and in the scarcity of academic research under this approach. Secondly, the research represents potential importance for society due to the prominence of discussions about the TSE's role in combating disinformation in the 2022 election campaign, especially because it means a paradigm shift in relation to the 2018 Elections. , the study is characterized by a qualitative approach, using the technique of surveying bibliographic and documentary data, as well as normative, jurisprudential and statistical analysis. This is a study with epistemological purposes, as it involves analysis and apprehension of concepts related to the research object, and it is also an exploratory research, as it seeks to describe and explain the main parameters extracted from the TSE jurisprudence, and interdisciplinary, as it performs the integration of constituent parts of Political Science and Law. The study confirms the existence of a common hard core revealing a conceptual evolution of the electoral disinformation institute.